A hyperbranched structure formed by in-situ crosslinking of additive flame retardant endows epoxy resins with great flame retardancy improvement. (1st November 2021) - Peng, Xiaoliang; Liu, Quanyi; Wang, Donghui; Liu, Chuanbang; Zhao, Yang; Wang, Rui; Zheng, Penglun
Abstract: Epoxy resins (EPs) are a kind of widely used engineering materials, because of their excellent mechanical, chemical and physical properties, but a severe problem they faced is their poor flame retardancy. Single molecule flame retardants have met the bottleneck after the massive researches of the past decade, so, with the development of the polymer technology, hyperbranched flame retardants have been researched and applied, owing to their better and more efficient flame retardancy. Herein, a facile thermal treating procedure was applied to the cured EP thermosets which contained a crosslinkable additive flame retardant to in-situ form a hyperbranched flame retardant. The single molecule flame retardants with N/P elements and crosslinkable nitrile groups were synthesized through an easy method, and physically mixed with EP matrix. After the curing reaction of EP matrix, the thermosets were further treated with a thermal treating procedure, while transferring the single molecule flame retardant into hyperbranched flame retardant, the semi-interpenetrating network was formed at the same time. The flame-retardant properties have been measured by limiting oxygen index (LOI) tests, UL-94 vertical burning tests and cone calorimeter tests, the results showed the flame retardants were extremely efficient and greatly elevated the flame retardancy of EPs, since the 0.5 wt% content could make modified EP samples pass the UL-94 V-0 rate, and with 20 wt% content the LOI value reached 49.5 % and the peak heat release rate reduced for 71.6 % compared with pure EPs.